Modus Operandi of Simultaneous Covering Synthesis from Precursor Heterogeneity for Shelled Nanorods for Multipotent Cancer Theranostics. (27th December 2019) - Yim, Gyeonghye; Kang, Seounghun; Kim, Hyungjun; Kim, Young‐Jin; Gil, Yeong‐Gyu; Kim, Young‐Kwan; Min, Dal‐Hee; Jang, Hongje
Abstract: The synthesis of nanostructures using homogeneous precursors in the solution phase is widely used to achieve uniformity and well‐defined morphological control. However, drawbacks such as the lack of diversity due to the limited reaction rate modulation exist. One‐step, core–shell nanorod formation using simultaneous covering synthesis using solid and ionic heterogeneous precursors is proposed in this study. A Te‐Bi2 Te3 /TeO2 core–shell structure is successfully synthesized by precisely controlling various influencing factors, including concentration, temperature, and pH, and its physicochemical and photochemical properties are thoroughly investigated. The proposed nanostructure overcomes the oxidation susceptibility of Te and can be applied to multipotent cancer theranostics in vitro and in vivo in combination with computed tomography imaging. Abstract : Simultaneous core formation with a surface covering reaction is accomplished by using unconventional precursor heterogeneity conditions. The synthesized Bi–Te covered nanorod exhibits far better colloidal stability, cargo loading capacity, and photocatalytic activity than bare Te nanorods. In combination with computed tomography‐guided multiwavelength cancer theranostic features, the technique has its own potential in various fields.